The Effect of Self-Efficacy and Role Understanding on Teachers’ Emotional Exhaustion and Work Engagement in Inclusive Education in Macao (SAR) - Kuok, A. C. H.; Teixeira, Vitor; Forlin, Chris; Monteiro, Elisa; Correia, Ana (International Journal of Disability, Development and Education, 2020)
This study examined responses from 508 full-time teachers working in inclusive schools in Macao (SAR). The intention was to understand the teachers’ perceptions about their roles and how they responded to inclusive practices in their school. Teachers’ perceived levels of emotional exhaustion and cognitive work engagement were assessed in relation to several professional competencies (self-efficacy with using inclusive instruction, collaborating with parents and paraprofessionals, and managing disruptive behaviours), as well as the organisational variable of role understanding. Regression analysis showed that teachers’ self-efficacy with using inclusive instruction was found to be the most powerful negative predictor of emotional exhaustion; while self-efficacy for managing disruptive behaviours was a positive predictor of teachers’ cognitive work engagement. Teachers’ level of understanding of their role and that of their schools was a negative predictor of emotional exhaustion and a positive predictor of cognitive work engagement. Moreover, it further confirmed that the concept of co-existence between work engagement and burnout can be applied to inclusive teachers. Results were interpreted in relation to management in inclusive schools in Macao and were followed by a discussion on the implications of enhancing inclusive education.
1 citations (Crossref) [2022-09-21]

Home–School Collaboration in Assessment, Placement, and Individual Education Plan Development for Children With Special Education Needs in Macao: The Views of Parents - Correia, Ana; Teixeira, Vitor; Forlin, Chris (School Community Journal, 2021)
The aim of this study was to explore home–school collaboration in the areas of assessment, placement, and Individual Education Plan (IEP) development for children identified with disabilities or special educational needs (SEN) in Macao. Despite the noted benefits of parent–school partnerships from prior research, minimal research has been conducted from the perspective of parents of children with SEN to examine whether these partnerships materialize in the context of Macao. Participants included 115 parents of school-aged children diagnosed with SEN. They provided demographic information and completed a 36-item questionnaire derived from two validated instruments. The research identified a range of factors which hinder parental involvement in decision-making and in the inclusion of children with SEN in optimal ways in Macao schools. Parents indicated they were not receiving relevant information and assessment feedback from the teachers; they were minimally involved in the IEP process, and their children were not receiving one-to-one support, regardless of the type of placement. Parents also underlined issues related to the timing of assessment procedures. Parents of children attending special classes in regular schools voiced more satisfaction with support provision than parents of children following the full inclusion model. Recommendations about how services could be improved for greater parental involvement are discussed. Key Words: parental involvement, school–family collaboration, inclusion, special educational needs, Macao, Individual Education Plans, IEP

Exploring the participation and agency of students with special education needs in a Macau-Chinese secondary school - Correia, Ana M.; Forlin, Chris; Sio, Eva (Journal of Research in Special Educational Needs, 2022)
The research explores the perceptions of five secondary school students with special education needs (SEN) about their participation in learning, group membership, and agency within an inclusive school in Macau SAR. This goal is achieved by using students' voices documented in open-ended interviews and is underpinned by the conceptual framework of heutagogy. The aim is to shed light on students' perceptions on school effectiveness in supporting their needs through successful participation and agentic possibilities. Findings showed that students were more prone to social rejection and being isolated or bullied than their peers. They were struggling to feel included or participate, their needs were only partially being met, and they had few opportunities to exert influence on their educational trajectories. Recommendations are provided to assist educators and schools in enhancing students with SEN to connect to the learning process and community, with the provision of appropriate learning adjustments and more active approaches to ensure their acceptance by mainstream students, including the formation of coaching peers to assist in developing social and academic skills under teacher's scaffolding practices. This study highlights the contribution of the heutagogical perspective to advance research on the participation and agency of students with SEN in mainstream schools.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/1471-3802.12566
Keywords: Macau SAR; Special education needs; agency; disability; inclusive education; participation; students' voice